Civilizational Analysis: Vytautas Kavolis and Benjamin Nelson - Noreika, Alvydas (Sociologija. Mintis ir veiksmas, 2004)
The article deals with famous Lithuanian sociologist Vytautas Kavolis (1930-1996) contribution to Civilization Analysis, one of the modern approaches to the civilizational sociology. Vytautas Kavolis understanding of civilization, its organization and dynamics, as well the methodology developed by him, is compared with that of Benjamin Nelson (1911-1977), a begetter of Civilization Analysis. As compared to B. Nelson, V. Kavolis proposes not a few innovations. The most original parts of V. Kavolis civilizational sociology are conception of civilization’s organization and that of civilizational dynamics. Developing them V. Kavolis employs formalistic approach broadly. His attention is concentrated on the patterns of structural relationships between meanings (formal designs), theory-practice articulation modes and their changes. The least differences between V. Kavolis and B. Nelson are observable in the sphere of methodology of research of civilizations.
Keywords: civilization; culture; organization of civilization; formal constructions; principles of integration; civilizational processes